Evidence of celestial phenomena in Urartian cuneiform texts? - Grekyan, Yervand (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Unlike the ancient Mesopotamian cuneiform sources, there is no direct evidence of keeping records of celestial objects or astronomical phenomena in the corpus of the Urartian cuneiform texts. In spite of this, astral scenes are widely represented in religious symbolism and iconography of Urartian bronze art. An exceptional evidence of an Urartian cuneiform text could fill the lack of information, perhaps, pointing out the apparition of a comet.